DEALING WITH MIXED-ABILITY CLASSES IN LANGUAGE TEACHING (Ustozlar uchun, 2026)
Mixed-ability classes have become a common phenomenon in modern language education due to differences in learners’ language proficiency, motivation, learning styles, and educational backgrounds. Teaching students with varying abilities in the same classroom presents significant challenges for language teachers, including classroom management difficulties, material selection, and maintaining student motivation. However, mixed-ability classrooms also create opportunities for collaborative learning and communicative interaction. This article discusses the nature of mixed-ability classes, the major challenges teachers face, and effective strategies for managing diverse learners in language teaching. Particular attention is given to differentiated instruction, communicative language teaching, group work, technology integration, and learner-centered approaches. The article concludes that successful management of mixed-ability classes requires flexibility, creativity, and supportive classroom environments that encourage all learners to participate and progress according to their abilities.